Tolstoy’s Happy Children of Peace. The Wartime Translation of 'Sebastopol in December' (1855) - Regniers, Gaëtan (Vertimo studijos, 2023)
A geopolitical clash between Russia and other European powers, the Crimean War (1854–1856) witnessed the first mediatized armed conflict in modern history. During the war, the young Lev Tolstoy wrote and published three Sevastopol Sketches, based on his wartime experiences in the besieged port of Sevastopol. Upon publication, the first of the stories was translated into French and published within a fortnight. Une journée à Sévastopol en décembre 1854 featured in Le Nord, a Brussels newspaper covertly operated by the Russian government. An in-depth analysis of the translation shows that the text was abridged and carefully groomed to serve Russia’s interests and Tolstoy’s patriotism made way for an appeal to the target audience, designated as ‘happy children of peace.’ Elaborating on the origins of the translation and its publishing context, I argue that this particular translation needs to be read both as an act of soft power and as an act of diplomacy. If the target text is considered as a historical document among other sources, empirical historical research can prove beneficial to the discipline and move forward the debate on Translation Studies’ approach to highly ideological contexts, in particular translations in periodicals.
Keywords: Russia; translation; periodicals; Tolstoy; Crimean War